CONCEALMENT OF BIRTH BY SECRET DISPOSAL OF DEAD BODY IN THE LAVATORY OF AIRPLANE: A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2020)
Concealment of birth is the act of a parent (or other responsible person) failing to report the birth of a child. The term is sometimes used to refer to hiding the birth of a child from friends or family, but is most often used when the appropriate authorities have not been informed about a stillbirth or the death of a newborn. This is a crime in many countries, with varying punishments. In India according to Section 318 of IPC (Indian Penal Code)- Whoever, by secretly burying or otherwise disposing of the death body of a child whether such child die before or after or during its birth, intentionally conceals or endeavours to conceal the birth of such child, shall be punished with imprisonment of either description for a term which may extend to two years, or with fine, or with both. Child abandonment is the practice of relinquishing interests and claims over one’s offspring in an illegal way with the intent of never again resuming or reasserting guardianship over them. Baby dumping refers to parents leaving a child younger than 12 months in a public or private place with the intent of terminating their care for the child.
Keywords: Concealment of birth; Secret disposal of dead body,; Lavatory of airplane; Section 318 IPC; Child abandonment; Baby dumping; Self delivery in flight; Taekwondo player